KETERIKATAN KARYAWAN MERUPAKAN ALTERNATIF, KETIKA KEPUASAN KERJA DAN KOMITMEN TIDAK CUKUP UNTUK MENINGKATKAN KINERJA ORGANISASI - Saroyeni Piartrini, Putu (PIRAMIDA; Vol. 7, No.1 Juli 2011)
Management is challenged by effeciency and quality to stay in competition.Building efficiency and quality based on employee satisfaction and employeecommitment is not sufficient today. Management needs Employee engagement toimprove its efficiency and quality of its operation sustainably. Employee engagement isrelatively new construct in employee behavior research, because it is found bypractitioner. It is defined as The harnessing of organization members selves to theirwork roles. In engagement people employee and exprese themselves physically,cognitively and emotionally during role performance.Employee engagement is neither similar to Organizational Citizenship norEmployee Commitment. It is different on its role on relationship between job satisfactionand organization citizenship behavior and intention to quit. Having reveiwed relatedarticles, among effect of job characteristics, Justice and organization support, employeeengagement significantly influenced by justice and organization support and leadership.To stimulate employee engagement, Management have to develop participativeleadership style, support their employee sufficiently and implement justice policyspesifically procedural justice in consisten way for every aspect of its functionalmanajemen. Employee engagement has positif relationship with Organizationperformance.
Keywords: Employee Engegement, Citizenship behavior, Job satisfaction, Organization Commitment and Organization Performance